La configuración narrativa de Silent Hill, Silent Hill 2 y Silent Hill 3 desde la intertextualidad: análisis del videojuego como texto multimodal - Riofrio Simancas, Dayana Pamela (2024)
This research focused on the intertextual and multimodal analysis of three video games from the Silent Hill series. The study employed a qualitative documentary design, considering characters, spaces, visual, auditory, and ludo narrative components that constitute these video games. The research findings indicated a close intertextual relationship between Silent Hill characters and mythological as well as contemporary characters. Regarding the spaces, various mythological references were found within the town, depicting liminal spaces similar to Judeo-Christian tradition, places and rituals belonging to Egyptian mythology, as well as the representation of Aztec mythology in characters and objects. Concerning the multimodality of the video game, three crucial components differentiating these video games as multimodal texts were highlighted. The auditory component considered character dialogues and ambient music, with emphasis on the radio sound accompanying all installments. The visual component emphasized the importance of space, analyzing the liminal and claustrophobic spaces depicted in the video game, reinforcing the atmosphere of terror. Finally, the ludo narrative component identified the mechanics, setting, and characters that constitute a message in themselves, reinterpreting the work through its actions and player actions. It is concluded that the analysis of intertextuality and multimodality in video games is a necessary investigation to comprehend video games as cultural phenomena, similar to cinema and literature. Therefore, it should be thoroughly studied and evaluated from various perspectives, whether literary, cinematic, or ludo narrative.